Hijacking T cell differentiation: New insights in TLX function in T-ALL - King, Bryan (2012)
TLX1 and TLX3 are two closely related homeobox transcriptional repressors frequently misexpressed and translocated in T cell acute lymphoblastic leukemia (T-ALL). In this issue of Cancer Cell, Dadi et al. provide new insights into how these factors are recruited by ETS-1 to the TCRα enhancer and actively repress differentiation.